Legitimacy and revolution in a society of masses : Max Weber, Antonio Gramsci, and the fin-de-siècle debate on social order /: Max Weber, Antonio Gramsci, and the fin-de-siècle debate on social order. (2017) - Giglioli, M. F. N, 1976-
No abstract available